VEGF Genetic Polymorphisms May Contribute to the Risk of Diabetic Nephropathy in Patients with Diabetes Mellitus: A Meta-Analysis - Li Sun; Quan Yuan; Ning Cao; Wei Guo; Li Yao; Jiang-Min Feng; Jian-Fei Ma; Li-Ning Wang (The Scientific World Journal)
Objective. This meta-analysis aimed to investigate a comprehensive and reliable conclusion on the correlations of single nucleotide polymorphisms (SNPs) in the vascular endothelial growth factor (VEGF) gene with the risk of diabetic nephropathy (DN) in patients with diabetes mellitus (DM). Methods. We screened PubMed, Embase, Web of Science, Cochrane Library, CISCOM, CINAHL, Google Scholar, CBM, and CNKI databases for those relevant studies that investigated the association of 14,945 subjects with clinicopathological parameters in gastric cancer. Results. Eleven case-control studies that met all inclusion criteria were included in this meta-analysis. A total of 14,945 subjects were involved, including 3,049 DN patients and 11,896 DM patients. Our meta-analysis results revealed that VEGF rs2010963 and rs3025039 polymorphisms might contribute to the risk of DN in DM patients. Ethnicity-stratified analysis suggested that VEGF genetic polymorphisms were associated with an increased risk of DN among Asians. However, we found no correlations of VEGF genetic polymorphisms with susceptibility to DN among Caucasians. Conclusion. Our findings suggest that VEGF rs2010963 and rs3025039 polymorphisms may contribute to the risk of DN in DM patients, especially among Asians. Thus, VEGF genetic polymorphisms could be useful biomarkers for early diagnosis of DN in DM patients.